2021
DOI: 10.3389/fnins.2021.678909
|View full text |Cite
|
Sign up to set email alerts
|

Congruency of Information Rather Than Body Ownership Enhances Motor Performance in Highly Embodied Virtual Reality

Abstract: In immersive virtual reality, the own body is often visually represented by an avatar. This may induce a feeling of body ownership over the virtual limbs. Importantly, body ownership and the motor system share neural correlates. Yet, evidence on the functionality of this neuroanatomical coupling is still inconclusive. Findings from previous studies may be confounded by the congruent vs. incongruent multisensory stimulation used to modulate body ownership. This study aimed to investigate the effect of body owne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 65 publications
0
13
1
Order By: Relevance
“…Importantly, neuroimaging studies have shown that brain areas linked with embodiment overlap with those involved in motor control (Ehrsson et al 2005;Wise 1985;Zeller et al 2016). Thus, increasing virtual embodiment through specialized displays-such as HMDs (Spanlang et al 2014)-might be an effective tool to promote brain plasticity and improve motor (re)learning (Grechuta et al 2017;Odermatt et al 2021;Shibuya et al 2018).…”
Section: Potential Benefits Of Hmds For Motor Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, neuroimaging studies have shown that brain areas linked with embodiment overlap with those involved in motor control (Ehrsson et al 2005;Wise 1985;Zeller et al 2016). Thus, increasing virtual embodiment through specialized displays-such as HMDs (Spanlang et al 2014)-might be an effective tool to promote brain plasticity and improve motor (re)learning (Grechuta et al 2017;Odermatt et al 2021;Shibuya et al 2018).…”
Section: Potential Benefits Of Hmds For Motor Trainingmentioning
confidence: 99%
“…Although several studies have used HMDs to show beneficial effects of virtual embodiment on motor task performance (Grechuta et al 2017;Odermatt et al 2021;Shibuya et al 2018), they did not primarily aim at studying how different visualization technologies affect embodiment levels.…”
Section: Hmds Enhance Embodimentmentioning
confidence: 99%
“…Participants with relatively weak illusion effects likely experienced an enhanced sensory mismatch in the stone condition than participants with stronger illusion effects. Incongruency of information in virtual environments has previously shown to hamper reaction times and motor performance, independently of the experienced body ownership over the avatar ( Odermatt et al, 2021 ). The facilitated versus hampered feedforward movement depending on the illusion strength could explain why, across the whole group, marginal overall slowed movement initiations were found in the stone versus human avatar condition.…”
Section: Discussionmentioning
confidence: 99%
“…The rubber hand illusion has, for example, been replicated numerous times in VR –in the so-called “virtual hand illusion”– where congruent (e.g., haptic or tactile) feedback is provided to the real hand of the participant together with visual feedback in VR [i.e., on the hand of the avatar seen by the participant; ( Slater, 2008 ; Perez-Marcos et al, 2009 ; Sanchez-Vives et al, 2010 ; Pyasik et al, 2020 ; Jeong and Kim, 2021 ; Kanayama et al, 2021 )]. Further, the high visuo-motor or visuo-proprioceptive synchrony –i.e., the high spatial and temporal correlation between the performed movement and the visually perceived feedback on the display– in immersive VR has also been shown to induce strong embodiment over the avatar, without the need of additional tactile stimulation ( Sanchez-Vives et al, 2010 ; Carey et al, 2019 ; Odermatt et al, 2021 ). Notably, immersive VR, together with additional sensory feedback, can be used to induce embodiment over “unrealistic” avatars ( Kilteni et al, 2012b ; Preston and Newport, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation